Properties of Nanostructured TiCN and TiCN-TiAl Hard Materials Sintered by the High-Frequency Induction-Heating - Shon, In-Jin; Kang, Hyun-Su; Du, Song-Lee; Hwang, Junyeon; Lim, Jae-Won (JAPAN INST METALS, 2013)
In the case of cemented TiCN, Ni or Co is added as a binder for the formation of composite structures. However, the high cost of Ni or Co and the low corrosion resistance of the TiCN-Ni cermet have generated interest in recent years for alternative binder phases. In this study, TiAl was used as a binder and consolidated by the high-frequency induction heated sintering (HEMS) method. Highly dense TiCN-TiAl with a relative density of up to 100% was obtained within 2 min by BEES under a pressure of 80 MPa. The method was found to enable not only the rapid densification but also the inhibition of grain growth preserving the nano-scale microstructure. The average grain sizes of the sintered TiCN and TiCN-TiAl were lower than 100 urn. The addition of TiAl to TiCN enhanced the hardness and toughness due to increase of relative density.
Keywords: MECHANICAL-PROPERTIES; WC-CO; CONSOLIDATION; COMPOSITE; ALLOYS